The Effect of Cooperative Learning Teams-Games-Tournaments (TGT) Type on Collaboration Skills and Learning Achievement Class V Students in Science Subjects at SDN Penarang 01 and SDN Penyaran 04 Sidareja District, Cilacap District - Praise Astuti; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims (1) to analyze the influence of cooperative learning of the Teams-Games-Tournaments (TGT) type on the collaboration skills of class V students in science and science subjects at Penyarang State Elementary Schools 01 and 04, (2) to analyze the influence of cooperative learning of the Teams type -Games-Tournaments (TGT) on the learning achievement of class V students in science and science subjects at Penyarang State Elementary School 01 and 04. Meanwhile, the research method used in this research is quantitative descriptive research and the research method used is the explanatory survey method. Collect data using a questionnaire and analyze the data statistically to test the questions and hypotheses raised. The results of this research are (1) There is an influence of Teams-Games-Tournaments (TGT) type cooperative learning on the collaboration skills of class V students in the subject IPAS at Penyarang State Elementary Schools 01 and 04 with the results of the independent t-test, obtained a significance value (p) of 0.008 (< 0.05). (2) There is an influence of cooperative learning of the Teams-Games-Tournaments (TGT) type on the learning achievement of class V students in the science and sciences subject at Penyarang State Elementary Schools 01 and 04 with the results of the independent t-test, a significance value (p) of 0.002 was obtained. (< 0.05) with a class average score of 78.